Advancing educational productivity : policy implications from national databases - Paik, Susan J. (Research in educational productivity., 2004)
Advancing Educational Productivity provides a wealth of critical analysis on educational matters at the local, state, national, and international levels. The authors have tackled issues such as educational productivity and achievement and other outcomes; forms of social capital in the home, school, and community; innovative measurement and design approaches to understanding achievement and similar outcomes; and international studies for understanding U.S. productivity. This book acquires greater timeliness with the passing of President George W. Bush's federal education legislation, the No Child Left Behind Act, intended to ensure that all children have a fair, equal and significant opportunity to obtain a high-quality education and reach, at a minimum, proficiency on challenging state academic achievement standards and state academic assessments.